Implementasi Sistem Permohonan Sertifikasi di Balai Besar Pulp dan Kertas - ADHIMA, MOCH FAUZAN; UMAROH, SOFIA (e-Proceeding FTI, 2024)
Information systems aim to provide information for decision making in planning, organizing, and controlling the operations of a company’s subsystems, as well as presenting organizational synergy in the process. Balai Besar Pulp dan Kertas (BBPK) conducts testing and certification of pulp and paper industry products through the conformity assessment institute called Pulp and Paper International Certification Services (PaPICS). Currently, BBPK already has a testing information system (SIP), but this system is unable to manage certification application data. Therefore, it is necessary to develop a certification application information system that will include managing applicant company data, certification application data, and the certification application review process. With this development, it is expected that BBPK can effectively and efficiently manage certification application data. Abstrak Sistem informasi bertujuan untuk memberikan informasi untuk pengambilan keputusan dalam perencanaan, pengorganisasian, dan pengendalian kegiatan operasi dari subsistem suatu perusahaan, serta menyajikan sinergi organisasi dalam prosesnya. Balai Besar Pulp dan Kertas (BBPK) melakukan pengujian dan sertifikasi produk industri pulp dan kertas melalui Lembaga Penilaian Kesesuaian yang disebut Pulp and Paper International Certification Services (PaPICS). Saat ini, BBPK sudah memiliki sistem informasi pengujian (SIP), namun sistem ini belum dapat mengelola data permohonan sertifikasi. Oleh karena itu, perlu dilakukan pengembangan sistem informasi permohonan sertifikasi yang akan meliputi pengelolaan data perusahaan pemohon, data permohonan sertifikasi, dan proses peninjauan permohonan sertifikasi. Dengan pengembangan ini diharapkan BBPK dapat mengelola data permohonan sertifikasi dengan efektif dan efisien.